Manufacturing process optimization and quality grading method of insulating paperboard for converter transformer. Issue 1 (1st April 2022) - Zhang, Shuqi; Yu, Xinru; Wu, Chao; Jia, Pengfei; Deng, Junyu; Cheng, Huanchao
Abstract: Oil paper insulation is the main form of transformer internal insulation. Different from the conventional transformer, the insulating paperboard bears a higher electric field component in the interior of the converter transformer. Therefore, the performance of insulating paperboard plays a vital role in the reliability of converter operation. Many insulation faults have occurred in the operation of UHV converter transformer. The production process and detection standard of conventional transformer insulating paperboard can not meet the operation requirements of UHV converter transformer under high field strength. In this study, the performance of insulating paperboard for UHV converter transformer was tested and compared. Combined with the series tests of micro properties, physical and chemical properties and electrical properties in the manufacturing process of insulating paperboard, the key manufacturing process of insulating paperboard is studied, and the process measures suitable for UHV converter transformer insulating paperboard are put forward. In addition, the comparison between the current test standard of insulating paperboard and the actual operation requirements is carried out, and the key performance test indexes of insulating paperboard applicable to converter transformer that are not covered in IEC standard are analyzed. The quality classification of insulating paperboard of UHV converter transformer and conventional transformer is carried out, and the selection scheme is provided. Insulating paperboard of class A is selected to be suitable for the design and manufacture of UHV converter transformer. The research results provide support for improving the performance of insulating paperboard of UHV converter transformer and ensuring the operation reliability of transformer.